A novel fibronectin binding site required for fibronectin fibril growth during matrix assembly - Sechler, Jan L. (The Rockefeller University Press, 2001)
Fibronectin (FN) assembly into a fibrillar extracellular matrix is a stepwise process requiring participation from multiple FN domains. Fibril formation is regulated in part by segments within the first seven type III repeats (III(1–7)). To define the specific function(s) of this region, recombinant FNs (recFNs) containing an overlapping set of deletions were tested for the ability to assemble into fibrils. Surprisingly, recFN lacking type III repeat III(1) (FNΔIII(1)), which contains a cryptic FN binding site and has been suggested to be essential for fibril assembly, formed a matrix identical in all respects to a native FN matrix. Similarly, displacement of the cell binding domain in repeats III(9–10) to a position close to the NH(2)-terminal assembly domain, as well as a large deletion spanning repeats III(4–7), had no effect on assembly. In contrast, two deletions that included repeat III(2), ΔIII(1–2) and ΔIII(2–5), caused significant reductions in fibril elongation, although binding of FN to the cell surface and initiation of assembly still proceeded. Using individual repeats in binding assays, we show that III(2) but not III(1) contains an FN binding site. Thus, these results pinpoint repeat III(2) as an important module for FN–FN interactions during fibril growth.